Serologi dan virologi virus avian influenza H5N1 pada kucing jalanan di Kota Bogor - Sri Murtini; R. Susanti; Ekowati Handharyani (Jurnal Ilmu Pertanian Indonesia, 2009)
Highly  pathogenic avian influenza (HPAI) H5N1 virus is a known pathogen in birds. Recently, the virus has been reported to cause sporadic fatal disease in tigers, leopards, and other exotic felids as well as domestic cats  in Thailand. The present study was carried out to investigate the presence of AI H5N1 virus infection in stray cats roaming around residential, traditional and chicken farms in Bogor, West Java. Ninety serum samples were tested using HI test to screened for the presence of antibody to AI H5N1. Virus isolation was done in SPF embrionated chicken eggs and identify using HI, AGP and RT-PCR. The results showed that 18,9% of stray cats developed antibodies against H5 with geometric mean titre 23,1 . Stray cats lived in traditional markets 18–40% developed antibodies in the titre ranging from 22,8  to 24,5. Only two out of nine stray cats which lived in chicken farm developed low antibody titres again H5 (21). None of the stray cats lived in residencial area have developed antibodies against H5. This study revealed that stray cats have been contact with AI H5. Avian influenza H5 viruses were isolated in eight out of 33 pooled of rectal swab samples. The viral cleavage site sequences are CCTCAAAGAGAGAGC AGAAGAAAGAAGAGAGGT which represent amino acid sequences of PQRESRRKKRG. Based on the cleavage site sequence, the isolates are similar with the AI H5 virus subtype isolated from human in Indonesia during 2005–2007.